A benthic macroinvertebrate multimetric index for Chilean Mediterranean streams. (August 2018) - Fierro, Pablo; Arismendi, Ivan; Hughes, Robert M.; Valdovinos, Claudio; Jara-Flores, Alfonso
Graphical abstract: Highlights: Anthropogenic perturbations in Chilean streams can be assessed using a multimetric index. We created a four-metric MMI based on aquatic macroinvertebrates. This simple index discriminates very well between reference and impaired sites across an extensive geographical area. Abstract: Increased anthropogenic disturbances affecting streams worldwide have resulted in declines of freshwater biodiversity. Mediterranean ecoregions are very sensitive to such disturbances because of their high levels of natural hydrological variability and increasing trends in human population growth. The use of aquatic macroinvertebrate assemblages as bioindicators is a commonly applied approach for evaluating water body condition. However, extensive use of macroinvertebrates across similar ecoregions may be limited because of natural local differences in biodiversity and differing anthropogenic disturbances. Here, we present a multi-metric index (MMI) based on macroinvertebrate assemblages from Chilean Mediterranean streams. To evaluate the relative level of disturbance among sampling sites with respect to multiple anthropogenic perturbations, we used an integrated disturbance index based on catchment and local scale disturbances. We sampled 95 sites from streams and rivers during the 2016 austral summer including 26 least-disturbed reference sites, 13 highly disturbed sites, and 56 intermediately disturbed sites. In addition, we re-sampled 14 sites during winter and spring to validate our findings. Using a set of screening criteria, we evaluated 74 candidate macroinvertebrate metrics, representing diversity, composition, trophic structure, and tolerance to pollution. The resulting MMI included Diptera taxa richness, total macroinvertebrate density, number of Ephemeroptera-Plecoptera-Trichoptera individuals, and predator taxa richness. The final MMI scores classified the 95 sampling sites into three categories of biotic condition, including good (n = 46), fair (n = 18), and poor (n = 31). Our approach is transferable to other rivers in the region and is a sufficient tool to evaluate the condition of sites affected by several human perturbations at both local and catchment scales in Chilean Mediterranean streams.